Cortisol, moderated by age, is associated with antidepressant treatment outcome and memory improvement in Major Depressive Disorder: a retrospective analysis - Jain, Felipe A. (Psychoneuroendocrinology, 2019)
BACKGROUND: Studies testing the relationship between cortisol levels, depression, and antidepressant treatment response have yielded divergent results suggesting the possibility of moderators of a cortisol effect. Several studies indicate that age may moderate the relationship between cortisol and depression. In patients with Major Depressive Disorder (MDD), we studied the interactive effects of age and cortisol in association with MDD diagnostic status and mood and memory response to antidepressant treatment. METHODS: Serum cortisol levels in 66 unmedicated patients with MDD and 75 matched healthy controls (HC) were measured at baseline and retrospectively analyzed. Logistic regression was used to determine an association of age, cortisol and their interaction with MDD diagnosis in the pooled sample of MDD and HC participants. Thirty-four of the MDD participants (age range: 19- 65 years; median: 36) underwent treatment with a selective serotonin reuptake inhibitor (SSRI) for 8 weeks. Clinician and self-ratings of depression symptoms, as well as tests of verbal and visual delayed recall were obtained at baseline and post treatment. Moderation analyses determined the effect of age on the relationship between baseline cortisol and treatment outcome. RESULTS: Cortisol, moderated by age, was associated with MDD diagnosis (p<.05), treatment-associated reduction of depression symptoms (p<.001) and improvement of delayed recall (p<.001). Modeling the Cortisol X Age interaction suggested that for participants below the median age of our sample, lower cortisol levels were associated with a lower rate of MDD diagnosis and higher antidepressant effects. On the contrary, in those above the median sample age, lower cortisol was associated with a higher rate of MDD and less improvement in depression symptoms and memory performance. CONCLUSIONS: Our results add to the body of literature suggesting that age might be an important factor in moderating the relationship between peripheral cortisol levels, depression, cognition, and prognosis. These results indicate that previous disparities in the literature linking peripheral cortisol levels with depression characteristics and treatment response may critically relate, at least in part, to the age of the participants studied.